2019
DOI: 10.15695/jstem/v2i1.20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Academic Performance Measures of HSTA Participants with Non-HSTA Participants: Is It Possible to Narrow the African American-White Achievement Gap?

Abstract: Historically, African American and other underserved students encounter academic challenges in pursuit of a college degree-one of which is their performance on standardized tests. This paper analyzes College Grade Point Averages (CGPAs), ACT Composite (ACTC), and SAT Total (SATT) scores of students who participated in the Health Sciences and Technology Academy (HSTA), an out-of-school-time (OST) program, and Non-HSTA (NHSTA) students attending West Virginia University. Traditionally, OST programs provide acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article described positive outcomes associated with the program. Since then, numerous studies have highlighted the program's success over two decades, including HSTA students exhibiting higher performance in college (McKendall et al, 2019), greater persistence in college (McKendall et al, 2000), greater persistence in STEM majors (McKendall et al, 2000), higher standardized test scores in high school (Smith-Branch et al, 2018), increasing recruitment of underserved students into the STEM workforce (Griffith, 2019;McKendall et al, 2014), and increasing health literacy and healthy behaviors among participants and their families (Chester et al, 2018).…”
Section: Key Strategies 4-7: the Skills Building Rsmentioning
confidence: 99%
“…This article described positive outcomes associated with the program. Since then, numerous studies have highlighted the program's success over two decades, including HSTA students exhibiting higher performance in college (McKendall et al, 2019), greater persistence in college (McKendall et al, 2000), greater persistence in STEM majors (McKendall et al, 2000), higher standardized test scores in high school (Smith-Branch et al, 2018), increasing recruitment of underserved students into the STEM workforce (Griffith, 2019;McKendall et al, 2014), and increasing health literacy and healthy behaviors among participants and their families (Chester et al, 2018).…”
Section: Key Strategies 4-7: the Skills Building Rsmentioning
confidence: 99%
“…These students have a unique voice and provide an important perspective to the conversation on equity and access to education. Comparison studies of HSTA students to non-HSTA populations have shown statistically significant differences favoring HSTA participants on standard-ized test scores (McKendall et al, 2019;Smith et al, 2018). Thus, they are self-motivated and have a desire to achieve.…”
Section: Introductionmentioning
confidence: 99%